STUDY OF FRENCH LANGUAGE LEARNING DIFFICULTIES IN HOSPITALITY STUDENTS AT MEDAN TOURISM POLYTECHNIC - Br Sinaga, Wirnawati (Jurnal Ilmiah Akomodasi Agung, 2025)
This study aims to identify the forms of difficulties faced by hospitality students in learningFrench, analyze the causal factors, and formulate effective learning strategies to overcome these obstacles. The method used is descriptive qualitative with the main instrumentinthe form of a questionnaire filled out by87 respondents of students of the Hospitality Department of the Medan Tourism Polytechnic. Data were analyzed through frequency tabulation and triangulation too btain more comprehensive results.The results ofthe study indicate that the main forms of difficulties experienced by student sinclude difficulties in memorizing vocabulary, understanding grammar, pronouncing words correctly, and forming simple sentences.These difficultiesare exacerbated by a lack of confidence in speaking, low learning motivation, non-contextual teaching methods, limited learning media, and minimal opportunities for language practice in and outside the classroom.As a solution, this study recommends communicative and project-based learningstrategies, such as hotel service simulations, pattern eddialogues, and the use of audio-visual media and digital platform stostreng the nunderstanding and pronunciation. The application ofthis strategyis considered effective in increasing students'interestin learning, practical skills, and confidencein using French in the hospitality context.